Pelatihan Peningkatan Literasi Membaca Kritis untuk Penguatan Kompetensi Profesional Guru Sekolah Menengah Atas - Fitrawati, Fitrawati; Zainil, Yetti; Ratmanida, Ratmanida; Tressyalina, Tressyalina (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2025)
The aim of this community service activity is to develop the professional competence of teachers from the critical reading literacy aspect of high school language teachers in Koto Tangah Padang sub-district (SMA Negeri 7, SMA Negeri 8, and SMA Negeri 13 Padang). The main problems that inspired this activity were 1) lack of teacher professional skills in teaching critical reading literacy, 2) lack of teacher understanding of strategies for teaching critical reading literacy, and 3) lack of media and critical literacy space in schools. To increase teacher literacy, the service team uses four stages of training, namely: a) planning stage, b) implementing stage, c) mentoring stage, and d) monitoring and evaluation stage. This activity involved 15 English and Indonesian teachers who took part in four face-to-face training sessions. The results obtained from this training were an increase in teachers' critical reading literacy skills based on a perception questionnaire distributed to teachers of 91.7% (very positive). It is hoped that later teachers will be able to design critical reading literacy teaching modules by applying good critical reading strategies and approaches to students.